Identifying Serious Games for Software Engineering Teaching in Brazil Through a Systematic Mapping Study (Research, Society and Development, 2020)
In the teaching of Software Engineering (SE), serious games or educational games are becoming increasingly used tools to stimulate the learning of aspects related to the software development process. However, few games are applied in the classroom, as there is no synthesized information about which games can be used depending on the content of the SE taught. This paper aims to identify which educational games have been developed for teaching SE in Brazil. A systematic mapping was carried out on digital bases for teaching computer and software engineering, identifying 25 educational games. The results indicate that although there are games for teaching project management, software testing and software process, there is still a need for games that include new dynamics beyond the traditional ones (e.g. games based on questions and answers, boards and cards) and topics in the discipline.